Retail technology adaptation in traditional retailers: A technology-to-performance chain perspective - Muriani Emelda Isharyani; Bertha Maya Sopha; M. Arif Wibisono; Benny Tjahjono (Journal of Open Innovation: Technology, Market and Complexity, 2024)
Traditional retailers must immediately embrace and adapt technology to survive in the competitive retail industry as retail technology rapidly changes consumers’ buying habits and expectations. This study may be the first to apply the Technology-to-Performance Chain (TPC) to traditional retailers' technological adaptation in an emerging market. A developing country's traditional retailers were studied qualitatively. Most of traditional retail's ongoing technologies are the result of adaptation by combining existing technologies to local conditions or technology adoption improvements. Technology adaptation includes using PoS system software with a printer and barcode scanner to substitute modern retail cash registers, a combination of mobile apps and PoS system software to mimic mPoS, and adapted EDC for digital product transactions. This technology adaptation is meant to manage business processes and manage the business growth of traditional retail that has limited resources and unique additional services. Therefore, available technology should be adapted to ensure low complexity, compatibility, and reliance on technologies that are familiar to people in developing countries. Furthermore, the task-technology fit (TTF) component requires the support of traditional retailers’ awareness, effective partnerships with technology providers, and perceived technical competence to increase the utilization of adapted technology and achieve the expected performance which includes inventory data clarity, increased retail revenue, and time savings.